Strategies to Increase EDOO Application New Users as a Form of Promotion of Digital Library Services at SMAN 15 Bandung - Anisah Putri Agsiya (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
The Library of SMA Negeri 15 Bandung has used the Edoo platform as a form of digital library implementation. The library has provided hundreds of e-libraries that can be used by all school members. Due to a shortage of users, the Edoo platform in the SMA Negeri 15 Bandung library experienced difficulties in developing. As a result, the various contents and library materials available cannot be used optimally. To increase these users, a good promotion strategy is needed. This study used is descriptive qualitative method. Edoo is an educational platform that has various management services at the school level, equipped with online and offline classes, a digital library, and special social media features that can be used by school members. Edoo has various advantages which make it easier for libraries and schools to use and utilize it. In the Edoo promotion strategy at the SMAN 15 Bandung library, There are a number of possible activities, including creating a brief introductory video for Edoo, movies on how to install applications, and videos on how to use Edoo, including using services and borrowing libraries through applications. The video will be distributed via the library's Instagram using the school's digital madding. It is preferable if the teacher participates in and helps with this Edoo promotion. Since encouraging students to utilize and access programs to support teaching and learning activities requires instructor participation.